Project Implementation Faciliting Tenants Keripik Aminah and Es Doger Mak Andak at Polbeng Business Expo Chapter II - Suri Wahyuni; M. Alkadri Perdana (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in driving economic growth and improving community welfare, but still face various obstacles, particularly in terms of marketing and business management. This study aims to examine the implementation of the tenant facilitation project for Keripik Aminah and Es Doger Mak Andak in the POLBENG Business Expo Chapter II. The method used is a quantitative descriptive approach with a project-based method, which includes the creation of profile videos, promotional videos, product catalogs, the application of digital marketing, the use of the QRIS non-cash payment system, and the preparation of bookkeeping and financial reports during the expo activities. Data was collected through observation, documentation, financial reports, and questionnaires, then analyzed using descriptive statistics, validity tests, reliability tests, and correlation analysis. The results of the study indicate that the implementation of digital promotion and participation in business expos have a positive effect on consumer purchasing decisions and increased sales for MSMEs. In addition, the implementation of systematic financial accounting and the use of QRIS can improve operational efficiency and ease of transactions. Thus, POLBENG Business Expo Chapter II contributes significantly to supporting the growth and sustainable development of the Keripik Aminah and Es Doger Mak Andak MSMEs.